Promoting Brain Health in Teacher Training Programs: A Case Study - Marikar, Faiz (Program Studi Psikologi Islam, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
General Sir John Kotelawala Defence University (KDU) pioneered preventive brain health and mental well-being by integrating Life’s Ten Principles into the Certificate in Teaching in Higher Education (CTHE) program during the 2024 Preventive Brain Health Week. The pilot involved 40 early-career academics who participated in interactive lectures, practical sessions, and reflective teaching portfolios focusing on holistic lifestyle factors such as healthy eating, physical activity, sleep hygiene, stress management, metabolic health, and social engagement. The findings suggest that feedback from students and young academics was used to inform decisions regarding program improvement. Furthermore, participants reported that integrating brain health activities may support professional development, teaching effectiveness, and mental resilience, contributing to a healthy, happy, and effective learning environment